The effect of flexibility exercises, static balance, eye-hand coordination on petanque shooting results - Kurniawan, R.; Junaidi, S.; Hidayah, T. (Jurnal Olahraga, 2019)
Several factors of the physical condition influence the given exercise, from various forms of flexibility training togok, static balance, and eye-hand coordination. These factors exist in the preparation of the given exercise program. This study aims to reveal the effect of togok flexibility exercises, static balance, and eye-hand coordination on the results of shooting petanque athletes in Riau province. This study found that eye-hand coordination was low, and the results of the petanque shooting of Riau province athletes were low. This research uses a quasi-experimental method using an experimental design of treatment by Level 2 x 2, a factorial experiment involving two factors. The sample of this research is 32 male petanque athletes from Riau Province. The distribution of the sample groups using the matching pairing method. This data is then continued with requirements testing and analysis of variance and variance data (ANAVA) 2 x 2. The data analysis results show no difference in the effect between togok flexibility and static balance on the shooting petanque results, and there is no interaction between togok flexibility and eye coordination. Hands-on the results of the shooting. So it can be concluded that there is no significant interaction between togok flexibility exercises, static balance with eye-hand coordination on the shooting results of Petanque Riau athletes